An Evaluation of Current and Emerging Trends in Strategic Management - Ajami, Matt Mohsen (Digital Repository of Theses - SSBM Geneva, 2024)
This thesis examines current and emerging trends in strategic management, employing qualitative research methods to analyze their impact on organizational strategies. The study aims to identify major trends influencing strategic management practices and provide insights for decision-makers. The objectives of current research work are related to determining the major current trends in the strategic management of businesses, evaluating the contemporary business trends and contextual factors that are influencing strategic thinking and management of businesses and determining the challenges for strategic management in the present business environment. Through a systematic review approach and interviews with industry professionals, the research addresses specific objectives outlined in the study. The examination investigates the developing scene of key administration, taking into account factors like technological advancements, changing business environments, and shifting consumer behaviors. By analyzing these patterns, the current research work tries to propose practical suggestions for associations looking to adjust and flourish in dynamic business sectors. The examination procedure involves a precise survey of literature obtained from credible databases such as EBSCO host, Emerald, JSTOR, Google Scholar, ProQuest, and Elsevier. Pertinent catchphrases and expressions are used to channel distributions and select excellent data sources for information extraction. Moreover, interviews with administrative specialists give significant bits of knowledge into industry points of view. In this study, the total sample of the population is 150 articles and the total number of respondents for the interviews is ten. Findings from the study underscore the importance of aligning organizational strategies with contemporary trends to enhance competitiveness and sustainability. This is how it is tried to achieve the objectives of the current research work by exploring the concepts of strategic adaptation and innovation emerging as critical factors in navigating complex business environments. The study is also found to contribute to a deeper understanding of strategic management dynamics and offers actionable recommendations for decision-makers. So, this research aims to empower organizations with the knowledge and tools necessary to navigate strategic challenges and capitalize on emerging opportunities. By synthesizing relevant literature and gathering insights from industry experts, the study seeks to inform strategic decision-making and drive organizational success in today's ever-evolving business landscape. Keywords: strategic management, qualitative research methods, organizational strategies, strategic management practices, decision-makers, interviews, recommendations.